Playing with data differently: engaging with autism and gender through participatory arts/music and a performative framework for analysis - Shaughnessy, Nicola; Herbert, Ruth; Williams, Emma; Walduck, Jackie; von Jungenfeld, Rocio; Newman, Hannah (Frontiers in Psychology, 2024)
There are increasing demands for Participatory Arts-Based (PAB) programmes involved in health research to better evidence outcomes using robust quantitative evaluation methodologies taken from science, such as standardized questionnaires, to inform commissioning and scale-up decisions. However, barriers arise from interdisciplinary differences in values and contexts. Researchers navigate tensions between the practice-based evidence produced by the arts and the evidence-based practice sought by psychologists. Consequently, interdisciplinary arts-science collaborations need to produce alternative methods of evaluation better aligned to PAB approaches, combining systematic rigor with sensitivity to the values, contexts and strengths of this approach. This article centers on the development of an alternative transdisciplinary analytic tool, the Participatory Play Framework, undertaken as part of an arts-psychology collaboration for a research project investigating autism and gender through creative practices. We present details of three stages in the development of the PP-Framework: 1. preliminary emergence of the framework from initial video analysis of observational data from participatory music and sound workshops run for 6 adolescent autistic girls (aged 11-16); 2. identification and application of modes of engagement; and 3. further testing of the framework as an evaluation tool for use in a real-world setting, involving professional musicians engaged in delivery of a creative music project at a center for homeless people. The PP-Framework maps types of participation in terms of performative behaviors and qualities of experience, understood as modes of play. It functions as a vehicle for analyzing participant engagement, This is a provisional file, not the final typeset article providing a tool predicated on the processes of working in creative participatory contexts whilst also being sensitive to the aesthetic qualities of what is produced and capable of capturing beneficial changes in engagement. It offers a conceptual approach for researchers to undertake observation of participatory arts practices, taking account of embodied engagement and interaction processes. It is informed by understandings of autistic performativity and masking in conjunction with an ecological understanding of identity and sense making as being shaped by environments, social relations and sensing subjectivity. The framework has the potential to be a bi-directional tool, with application for both practitioners and participants.